Evidence-Based Education: Critical Analysis of Current Discussions - Busygina N.P.; Podushkina T.G.; Stanilevsky V.V. (Психолого-педагогические исследования)
The article analyzes the current discussions on how to define evidence and implement evidence-based practice in education. Despite their frequent use, the terms “evidence-based practice”, “evidence-based education” etc. remain something like “empty signs” the meaning of which still needs to be defined. The authors highlight several discussion topics regarding research for evidence-based practice and evidence-based process: hierarchical versus pluralistic conception of evidence; theoretical reasoning as evidence; top-down evidence-based practice versus bottom-up evidence-informed practitioner judgment; conception of research use as linear process of uptake or dissemination versus as bidirectional process by which research and practice mutually inform each other. It is presumed that although historically evidence-based approach was associated with an appeal to science primarily as an institution of prescription, in its actual versions the relationship between science and practice is much more complex.